ERCC2 rs13181 and ERCC1 rs11615 polymorphisms in non-small cell lung cancer patients in West Java: towards personalized medicine approaches - Afifah, Nadiya Nurul; Effendi, M. Fariz; Diantini, Ajeng; Barliana, Melisa Intan; Intania, Ruri (Institut Teknologi Bandung, 2025)
Non-Small Cell Lung Cancer (NSCLC) is a disease with a high incidence rate, low survival due to late diagnosis and treatment delays, and varying effectiveness of platinum-based chemotherapy. Individual responses to platinum-based chemotherapy are influenced by genetic polymorphisms in genes affecting pharmacokinetic and pharmacodynamic mechanisms. This study focuses on identifying polymorphisms in the ERCC2 and ERCC1 genes, which play a role in platinum pharmacodynamics, and their effects on chemotherapy response. The study involved 23 NSCLC patients conducted at Dr. H.A. Rotinsulu Lung Hospital in Bandung. Polymorphism data were obtained through genotype analysis using sequencing methods from prospective whole blood samples of patients, while chemotherapy effectiveness was assessed by evaluating chemotherapy response using the RECIST 1.1 method, and radiological response prediction and prognostic factors were determined through CYFRA 21-1 levels. The results showed an OR of 0.964 (95% CI: 0.160 - 5.795) for ERCC2 rs13181 CC + AC vs. AA against chemotherapy response evaluation by RECIST 1.1, and 0.722 (95% CI: 0.062 - 8.464) against CYFRA 21-1 values. Meanwhile, for ERCC1 rs11615, an OR of 0.268 (95% CI: 0.046 - 1.548) CT + TT vs. CC for RECIST 1.1 and 0.3 (95% CI: 0.026 - 3.427) for CYFRA 21-1 values were obtained. In clinical interpretation, it is known that variant alleles at rs13181 and rs11615 have potential for better chemotherapy response although not statistically significant (p>0.05), these results can be considered when assessing patient response to chemotherapy within six cycles. This study provides initial data and forms the basis for future comprehensive cohort observational research.